ANALISIS RESEPSI KECANTIKAN DALAM VIDEO YOUTUBE ABEL CANTIKA “WARDAH ONE BRAND MAKEUP TUTORIAL - Risa Nur Inayah; Ismandianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
YouTube is the second social platform after Facebook which has the most active users until January 2018 .. In addition, beauty tutorial content is one of the content that users are interested in. In humans, the word beauty is a word that can never be separated from a woman. Beauty or beauty itself is often based on two categories, such as: Inner Beauty (the beauty that is in). The research method used is a descriptive qualitative research type. This research was conducted by looking at Abel Cantika's Youtube video content "Wardah One Brand Make Up Tutorial" which was accessed on August 31, 2020. Based on the results of the research and discussion previously stated, the following conclusions can be drawn: (1) Dominant Hegomony Viewers, the meaning of the audience is as beauty content that is honest in expressing its opinion, has a good attitude in reviewing products and conveying correct assumptions and in accordance with the condition of the product used by Abel when conducting tutorials. (2) Negotiating viewers, they are helped by the video tutorial from Abel because it really helps them choose the products they will use and who are just starting to learn to benefit from using makeup. (3) Oppositional audience, and there were some students who opposed the rejection for various reasons such as the problem of conformity with the shape of the face or the contrasting preference of Abel.Keywords: Reception Analysis, Youtube, Beauty Vlogger